Contribuições de práticas de educação em saúde, junto as pessoas idosas participantes de um grupo de convivência - Santos, Rosemar Gollo dos (2023)
In the context of population aging, the relevance of health education stands out. Characterized by the protagonism and appreciation of the knowledge of those involved, health education can be carried out with groups of older adults. Thus, studies are needed to address the contribution of health education in coexistence groups, as one of the ways to promote healthy aging. The general objective of this dissertation is to identify the contributions of educational practices in health with older people who participate in a social group. Its specific objectives are: to characterize the sample of older adults regarding their profile; to develop educational practices in the form of thematic workshops on quality of life, with emphasis on food as a self-care practice, using images as the main methodological resource; and to identify meanings attributed by the older adults participating in the workshops, in order to understand the contributions of the educational process in self-care. The research carried out consists of a field study, exploratory and descriptive, with a qualitative approach. The population consisted of members of the Coexistence and Strengthening of Bonds Service, linked to the Social Assistance in a small town in the interior of Rio Grande do Sul, Brazil. Nine people participated in the study, all women, aged between 65 and 90 years, who met the inclusion criteria. The research process began with the application of a data collection form of the participants' profile, individually, at the residence of the elderly. Then, four health education workshops were held with the group, with an emphasis on food as a self-care practice. The use of images was at the center of the methodological proposal of the workshops. For the analysis of the results, the images (iconographic texts) produced in the last workshop were considered and the proposal called Transtextual Reading of Images (LTSI) was used. The research enabled the construction of an article, which, based on meanings attributed by the participants of the workshops, aims to understand the contributions of the educational process developed with regard to food as a self-care practice. As a result, the group workshops were potentializers of protagonism and exchange of knowledge, as well as constituted an opportunity to strengthen supportive relationships. Participants highlighted the relevance of social relationships and healthy eating appeared as a health care strategy, seen as a way to create and cultivate relationships, especially among family members. The importance of public policies that contemplate older people in their entirety is emphasized, providing autonomy and advancing in the perspective of healthy aging. Health education practices that are methodologically creative, with the use of different resources, such as the use of images, can contribute in this sense